60 let red. prof. dr. Matjaža Klemenčiča - Marković, Irena; Verbič Koprivšek, Maruša (Slavia Centralis, 2020)
The article covers the scientific research work of dr. Matjaž Klemenčič, professor of recent history and contemporary history at the Faculty of Arts, University of Maribor.
Keywords: Matjaž Klemenčič; scientific research work; celebrations; history; professor